PERAN LEMBAGA KEUANGAN MIKRO TERHADAP PENGUATAN USAHATANI KUBIS DI KECAMATAN SUKAPURA KABUPATEN PROBOLINGGO - Ana Arifatus Sa’diyah; Dyanasari Dyanasari (Jurnal Agribisnis Indonesia, 2014)
Basically, financial service institution in a form of micro financial institution (MFI) is strongly needed to support the rural economic development especially as an institution to facilitate the farming business cost. This is caused by the fact that most of farmers face the technology adoption since it is weak in capital budget. This condition happens on the cabbage farmers who is facing the eruption of Bromo Mountain in Sukapura District, Probolinggo Regency. The aims of this research are to investigate the conception of potatoes farm (cost, supply, benefits and R/C) factors that influence the vegetables farm productivity in Sukapura, dan the role of microfinance on farm. The research was conducted in Ngadisari and Ngadirejo with purposive sampling method. Data which is obtained from the research is analyzed using R/C and Cobb-Douglass function. The results show that potatoes farm is beneficial with R/C value >1, the vegetables production are influenced by seeds, land area, biofertilizer, labor, perticides and microfinance have significant role on helping the farm.